2022
DOI: 10.1101/2022.02.25.481974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An immunoPET probe to SARS-CoV-2 reveals early infection of the male genital tract in rhesus macaques

Abstract: Because of the recognized systemic nature of SARS-CoV-2 infection, a non-invasive and unbiased method is needed to clarify its spatiotemporal dynamics in vivo after transmission. We recently developed a probe based on the anti-SARS-CoV-2 spike antibody CR3022 to study SARS-CoV-2 pathogenesis in vivo. Herein, we describe its use in immunoPET to investigate SARS-CoV-2 infection of rhesus macaques. Using PET/CT imaging of macaques at different times post-SARS-CoV-2 inoculation, we demonstrate that the 64Cu-label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 75 publications
1
10
0
1
Order By: Relevance
“…Even in the animal models, subgenomic SARS-CoV-2 RNA was detected only in the intratesticular inoculated hamsters (65). Further, the suggestion that SARS-CoV-2 can infect testes of the rhesus macaques by Madden and colleagues was based on the staining of Spike protein (66) and does not confirm if testis can support active replication of the virus. Therefore, taken together, our data showing the total absence of SARS-CoV-2 virions in the media and no cell death in infected cells, provide direct evidence that SARS-CoV-2 cannot establish productive replication in different testicular cells in vitro.…”
Section: Discussionmentioning
confidence: 98%
“…Even in the animal models, subgenomic SARS-CoV-2 RNA was detected only in the intratesticular inoculated hamsters (65). Further, the suggestion that SARS-CoV-2 can infect testes of the rhesus macaques by Madden and colleagues was based on the staining of Spike protein (66) and does not confirm if testis can support active replication of the virus. Therefore, taken together, our data showing the total absence of SARS-CoV-2 virions in the media and no cell death in infected cells, provide direct evidence that SARS-CoV-2 cannot establish productive replication in different testicular cells in vitro.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study described a 64 Cu-labeled CR3022-F(ab′)2 probe based on the anti-SARS-CoV-2S-protein antibody CR3022 to study the dynamics of infection within the respiratory tract and uncover novel sites of infection in rhesus macaques. 31 A strong signal was observed in extrapulmonary organoids, such as the penis, testes, prostate, and pampiniform plexus. In addition, SARS-CoV-2 virus particles and essential structures have been found in several organs, such as the appendix, eyes, heart, and brain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that a 64 Cu-labeled probe could target spike proteins in the respiratory tract and extrapulmonary organs (penis, prostate, testis, and pampiniform plexus) of SARS-CoV-2-infected rhesus macaques. 31 In the present study, MHV-A59 serves as a surrogate for investigating the ability of the probe to detect the spike protein in extrapulmonary organ infection. Above all, the 64 Cu-labeled probe could be utilized for whole-body imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations